2005
DOI: 10.1073/pnas.0507596102
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein C1/C2, MeCP1, and SWI/SNF form a chromatin remodeling complex at the β-globin locus control region

Abstract: Locus control regions (LCRs) are regulatory DNA sequences that are situated many kilobases away from their cognate promoters. LCRs protect transgenes from position effect variegation and heterochromatinization and also promote copy-number dependence of the levels of transgene expression. In this work, we describe the biochemical purification of a previously undescribed LCR-associated remodeling complex (LARC) that consists of heterogeneous nuclear ribonucleoprotein C1͞C2, nucleosome remodeling SWI͞ SNF, and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40). It has been shown that the NuRD complex mediates the recruitment of the Ezh2-PRC2 complex and that the SWI/SNF complex physically interacts with subunits of the NuRD complex including Mi-2β, HDAC1/2, MTA2, and MBD3 (31,33,(41)(42)(43)(44). In addition, it has been reported that the association of the NuRD complex in regulatory regions that are co-occupied with the SWI/SNF complex is severely reduced in the absence of the SWI/SNF complex in various biological contexts, whereas the binding of the SWI/SNF complex is not affected by the NuRD complex (42,45).…”
Section: Discussionmentioning
confidence: 99%
“…MTA3, a subunit of the NuRD complex, is also known to interact with Bcl-6 and to inhibit Blimp-1 expression (40). It has been shown that the NuRD complex mediates the recruitment of the Ezh2-PRC2 complex and that the SWI/SNF complex physically interacts with subunits of the NuRD complex including Mi-2β, HDAC1/2, MTA2, and MBD3 (31,33,(41)(42)(43)(44). In addition, it has been reported that the association of the NuRD complex in regulatory regions that are co-occupied with the SWI/SNF complex is severely reduced in the absence of the SWI/SNF complex in various biological contexts, whereas the binding of the SWI/SNF complex is not affected by the NuRD complex (42,45).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the capacity of GATA-1 to bind multiple co-regulators, BRG1 is mobilized at the promoter more rapidly than other co-regulators in response to GATA-1 occupancy at the LCR. Given that BRG1 occupies the ␤-globin locus (28,36), is recruited to chromatin sites by GATA-1, interacts with GATA-1 (Fig. 4C), and is rapidly attracted by GATA-1 to the promoter (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GATA-1 interacts with multiple co-regulators (31), including FOG-1 (14,32), CREB-binding protein (CBP)/p300 (33), MED1 (34), and BRG1 (27,28), and all except MED1 have been shown to occupy the LCR (27,28,35,36). We tested whether ER-GATA-1 occupancy at the LCR and promoter is coupled to co-regulator recruitment at these sites.…”
Section: Progressive Assembly Of a Cell Type-specific Chromatin Loopmentioning
confidence: 99%
“…BRG1 exists in a MafK complex in MEL cells (Brand et al, 2004), and also in a b-globin LCR-associated chromatin remodeling complex (LARC) (Mahajan et al, 2005). LARC binds the HS2-Maf recognition element, occupies HS2 in K562 erythroleukemia cells, and has chromatin remodeling activity (Mahajan et al, 2005). BRG1 also binds EKLF, and the SWI/SNF complex is required for EKLF-mediated transcriptional activation in vitro (Armstrong et al, 1998;Kadam et al, 2000).…”
Section: Brg1mentioning
confidence: 99%
“…BRG1 exists in a MafK complex in MEL cells (Brand et al, 2004), and also in a b-globin LCR-associated chromatin remodeling complex (LARC) (Mahajan et al, 2005). LARC binds the HS2-Maf recognition element, occupies HS2 in K562 erythroleukemia cells, and has chromatin remodeling activity (Mahajan et al, 2005).…”
Section: Brg1mentioning
confidence: 99%